The Financial Perspective Study on Tax Avoidance - Hisar Pangaribuan; Jouse Fernando HB; Sukrisno Agoes; Jenny Sihombing; Denok Sunarsi (Budapest International Research and Critics University, 2021)
Practically, it is still found that there is a distinction of interest between government and taxpayers, where the government has an interest in collecting taxes as optimal as possible to be channeled in the public interest, while taxpayers try to pay tax as efficiently as possible for their individual benefits. This study employed a confirmatory descriptive approach with aims to find out wheter financial reasons urged taxpayers to do tax avoidance. The population in this study is the annual financial statements of manufacturing companies listed in Indonesia Stock Exchange. The data collected and processed using the ordinary least square approach. This study proposed that transfer pricing has no significant effect on tax avoidance, leverage has a significant effect on tax avoidance, profitability has a significant effect on tax avoidance, and sales growth has a significant effect on tax avoidance. While the result of the simultaneous test shows that the overall predictor has a significant effect on tax avoidance. The findings from this study are important inputs, especially for government tax recipients to pay more attention to the companies where profitability and sales growth are high, and when receivables shifts are more concentrated on receivables with related parties when compared to receivables from other parties, the such companies are tend to do tax efficiency by means of tax avoidance.